(untitled) (Journal of the College of Basic Education, 2025)
President Gamal Abdel Nasser called the war that erupted between Egypt and Israel after 1967 the "War of Attrition," meaning a depletion of Israel’s capabilities and proof that Egypt was wasting no time in regaining victory. It was also a response to the Israeli statement that the 1967 war was the war to end all wars, and that Arabs should pledge allegiance and obedience to them in cooperation with the United States. Egypt also saw the necessity of waging a war with Israel, but at the same time, it was in a state that did not permit a direct confrontation. Therefore, it aimed to prevent Israel from expanding its influence in Arab lands, viewing it as the beginning of a new victory and restoring Egyptian fighters’ confidence in their capabilities and weapons. During the War of Attrition, Egypt suffered from American support for Israel in all areas and sought to gain Soviet support to counter the support provided to Israel. The war served as a means of military rehabilitation and training for the Egyptian army, providing a close look at Israel’s capabilities and providing sufficient time to enhance the Egyptian army’s capabilities, which helped them achieve their victory in 1973.